genetically modulated, intrinsic cingulate circuit supports human nicotine addiction - Hong, L. Elliot; Hodgkinson, Colin A; Yang, Yihong; Sampath, Hemalatha; Ross, Thomas J; Buchholz, Brittany; Salmeron, Betty Jo; Srivastava, Vibhuti; Thaker, Gunvant K; Goldman, David; Stein, Elliot A (Proceedings of the National Academy of Sciences - PNAS, 2010)
Whole-genome searches have identified nicotinic acetylcholine receptor α5-α3-β4 subunit gene variants that are associated with smoking. How genes support this addictive and high-risk behavior through their expression in the brain remains poorly understood. Here we show that a key α5 gene variant Asp398Asn is associated with a dorsal anterior cingulate-ventral striatum/extended amygdala circuit, such that the "risk allele" decreases the intrinsic resting functional connectivity strength in this circuit. Importantly, this effect is observed independently in nonsmokers and smokers, although the circuit strength distinguishes smokers from nonsmokers, predicts addiction severity in smokers, and is not secondary to smoking per se, thus representing a trait-like circuitry biomarker. This same circuit is further impaired in people with mental illnesses, who have the highest rate of smoking. Identifying where and how brain circuits link genes to smoking provides practical neural circuitry targets for new treatment development.